Association of a Methanol Extract of Rheum undulatum L. Mediated Cell Death in AGS Cells with an Intrinsic Apoptotic Pathway - Hong, Noo Ri (J Pharmacopuncture, 2015)
OBJECTIVES: Rheum undulatum L. has traditionally been used for the treatment of many diseases in Asia. However, its anti-proliferative activity in cancer has still not been studied. In the present study, we investigated the anti-cancer effects of methanol extract of Rheum undulatum L. (MERL) on human adenocarcinoma gastric cell lines (AGS). METHODS: To investigate the anti-cancer effect of MERL on AGS cells, we treated the AGS cells with varying con¬centrations of MERL and performed 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays. Cell cycle analyses, measurements of the mitochondrial membrane potential (MMP), caspase activity assays and Western blots were conducted to determine whether AGS cell death occurred by apoptosis. RESULTS: Treatment with MERL significantly inhibited growth of AGS cells in a concentration dependent manner. MERL treatment in AGS cells leaded to increased accumulation of apoptotic sub G1 phase cells in a concentration dependent manner. In control cultures, 5.38% of the cells were in the sub G1 phase. In MERL treated cells, however, this percentage was significantly increased (9.95% at 70 μg/mL, 15.94% at 140 μg/mL, 26.56% at 210 μg/mL and 38.08% at 280 μg/mL). MERL treatment induced the decreased expression of pro-caspase-8 and -9 in a concentration dependent manner, whereas the expression of the active form of caspase-3 was increased. A subsequent Western blot analysis revealed increased cleaved levels of poly (ADP-ribose) polymerase (PARP) protein. Also, treatment with MERL increased the activities of caspase-3 and -9 compared with the control. MERL treatment increased the levels of the pro-apoptotic truncated Bid (tBid) and Bcl2 Antagonist X (Bax) proteins and decreased the levels of the anti-apoptotic B-cell lymphoma 2 (Bcl-2) protein, whose is the stabilization of mitochondria. However, inhibitions of p38, extracellular signal regulated kinases (ERKs) and C-Jun N-terminal kinases (JNK) by MERL treatment did not affect cell death. CONCLUSION: These results suggest that MERL mediated cell death is associated with an intrinsic apoptotic pathway in AGS cells.